Using carbon finance to support climate policy objectives in high mountain ecosystems. (17th August 2016) - Ward, Adrian; Dargusch, Paul; Grussu, Giorgio; Romeo, Rosalaura
Abstract : Carbon markets and climate finance payments are being used to incentivize the mitigation of CO2 arising from anthropogenic land-use change in forests, marine ecosystems, and lowland grasslands. However, no such consideration has been given to how these 'carbon finance incentives' might be applied to mountain grasslands and shrublands, ecosystems that contain a substantial amount of carbon. These incentives amount to more than US350 billion per annum and could potentially support underfunded natural resource management (NRM) activities, which are urgently needed to address numerous stressors impacting these important ecosystems. In the mountain context, NRM activities could include adaptive grazing management, sustainable cropping, ecosystem preservation, ecosystem restoration, and engineered soil conservation measures. This article investigates the stressors, challenges, and priorities related to the NRM of carbon stocks in mountain grasslands and shrublands; why carbon markets and climate finance have not yet been utilized in this context; and, what is required to position mountain-based NRM activities as eligible for carbon finance incentives. Using surveys and interviews triangulated with a systematic literature review, the study found that carbon finance incentives are not well understood, both amongst mountain-focused experts and in the literature. The study also found the required technical methodologies, policy frameworks, and data to be largely undeveloped. This article proposes a top-down conceptual policy framework that can be used to develop key 'enabling factors' with the view of extending the eligibility of carbon markets and climate finance to NRM activities undertaken in mountain grasslands and shrublands in the same way that has been afforded to other ecosystems. Policy relevance This is the first study to explicitly highlight the important role that the mountain grasslands and shrublands might play in international climate policy, and how carbon finance mechanisms might support better NRM in these areas. It is also the first to investigate why these incentives have not been adopted thus far. The article concludes by proposing a novel top-down 'carbon incentive enabling' framework that could be driven by governments and mountain development focused organizations so as to capture some of the opportunities offered by carbon-based incentives, and help meet international climate policy objectives.